Tuesday

March 3, 2015

March 3, 2015

Posted by **miechelle** on Wednesday, April 13, 2011 at 5:34pm.

2x(5x-7y+3)-8x(2x+3y-1)

- math -
**Anonymous**, Wednesday, April 13, 2011 at 5:57pm2x(5x-7y+3)=2x*5x-2x*7y+2x*3=10x^2-14xy+6x

8x(2x+3y-1)=8x*2x+8x*3y-8x=16x^2-24xy-8x

2x(5x-7y+3)-8x(2x+3y-1)=10x^2-14xy+6x-(16x^2-24xy-8x)=10x^2-14xy+6x-16x^2+24xy+8x= -6x^2+10xy+14x

**Answer this Question**

**Related Questions**

Algebra 2 - Simplifiy the expression. sqrt4/49

Math - Expand the following binomials to look for patterns when expanding ...

Math - Expand the following expression. 3(m+2) + 4(6+m)

Log - Expand Log5(5squareroot x/7) the first 5 is a base how would you expand ...

Precalc - 1) expand (1+3x)^4 using the Binomial Theorem. 2) Use Pascal's ...

algebra - Expand. 2(x+10) It looks easy but what do they mean by expand?

human resources - with so many good foreign markets to enter, the question for ...

math b - i want to know if this is correct expand the following without using ...

maths - given that x+1/x=3 (a) expand (x+1/x)^3 and use your expansion to show ...

algabra - expand the following number (3a+2)3